2021
DOI: 10.33448/rsd-v10i8.17421
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile, antioxidant and antifungal activity of extracts from four medicinal plants of the Anacardiaceae family

Abstract: Phenolic profile, antioxidant and antifungal activity of extracts from four medicinal plants of the Anacardiaceae familyPerfil fenólico, atividade antioxidante e antifúngica de extratos de quatro plantas medicinais da família Anacardiaceae Perfil fenólico, actividad antioxidante y antifúngica de extractos de cuatro plantas medicinales de la familia Anacardiaceae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Such improvements suggest robust antidepressant activity, potentially mediated by the extract's alkaloidal and polyphenolic content, which interact with neurotransmitter pathways and reduce oxidative stress (Rebas et al, 2020). These results align with previous studies that reported similar antidepressant effects of A.occidentale extracts, which were attributed to its rich phytochemical content, particularly alkaloids and phenolics (Neves et al, 2021).…”
Section: Behavioral Outcomes In Depression-induced Male Micesupporting
confidence: 89%
“…Such improvements suggest robust antidepressant activity, potentially mediated by the extract's alkaloidal and polyphenolic content, which interact with neurotransmitter pathways and reduce oxidative stress (Rebas et al, 2020). These results align with previous studies that reported similar antidepressant effects of A.occidentale extracts, which were attributed to its rich phytochemical content, particularly alkaloids and phenolics (Neves et al, 2021).…”
Section: Behavioral Outcomes In Depression-induced Male Micesupporting
confidence: 89%
“…About 14 genera and 56 species, with 1 genus and 16 species endemic to Anacardiaceae, have been identified in Brazil. In the TSC, four medicinal species were identified, being rich in secondary metabolites with great therapeutic potential, such as antioxidant and antimicrobial effects (Antônio, 2016;Neves et al, 2021;Ramadan et al, 2010).…”
Section: Forest Biomass Sourcesmentioning
confidence: 99%
“…According to Neves et al. [ 19 ], ethanol extracts of Anacardiaceae species can be potential sources of new biotechnological products, acting as natural antioxidant and antifungal agents. However, UAE has been used to extract phenolic compounds and determine antioxidant activity from mulberry pulp [ 20 ], Genipap berry fruit pulp [ 21 ], jackfruit pulp [ 22 ], peaches fruit pulp [ 23 ], and apple pulp [ 24 ] among many other plants with nutritional or medicinal effects.…”
Section: Introductionmentioning
confidence: 99%